Pendekatan Komunikasi Persuasif di Akun TikTok @somethincofficial untuk Meningkatkan Interaksi dengan Pengikut - Serlly, Serlly (Ikatan Sarjana Komunikasi Indonesia, 2025)
This study explores the persuasive communication strategies used by the TikTok account @somethinc.official to build interaction and influence followers’ buying decisions. The researcher focuses on how the brand delivers persuasive messages through video content, captions, and comment section interactions. Previous studies agree that social media platforms like TikTok are effective in shaping consumer behavior through visual and interactive approaches. However, earlier research has not specifically highlighted how psychodynamic elements and meaning construction are used by local beauty brands in Indonesia. This study fills that gap by analyzing persuasive communication strategies based on two-way interaction used by the @somethinc.official TikTok account. This study aims to explain how persuasive communication strategies are applied in TikTok content to increase engagement and influence followers’ buying decisions. A descriptive qualitative method is used, with content analysis of videos, captions, and comments. The concepts used in this study include psychodynamic communication theory and meaning construction in social media. The results show that @somethinc.official consistently applies persuasive strategies through live streaming to create two-way interaction, casual language to build closeness with followers, and visual elements like the brand’s signature colors. Content such as product explanations, user reviews, and promotional offers like discounts has been effective in increasing engagement and encouraging purchases. These findings support the principles of persuasive communication and are relevant for other brands on similar platforms.